Selected persistent organic pollutants (POPs) in the rhizosphere of sewage sludge-treated soil: implications for the biodegradability of POPs. Issue 7 (7th June 2019) - Száková, Jiřina; Pulkrabová, Jana; Černý, Jindřich; Mercl, Filip; Švarcová, Andrea; Gramblička, Tomáš; Najmanová, Jana; Tlustoš, Pavel; Balík, Jiří
ABSTRACT: The impact of regular application of sewage sludge or farmyard manure on the organic contaminant loads in soil was assessed in a model rhizobox experiment. Two soils originating from a long-term field crop rotation and fertilizer experiment running since 1996 were used. The total polychlorinated biphenyls (PCBs), polycyclic aromatic hydrocarbons (PAHs), organochlorinated pesticides (OCPs), polybrominated diphenyl ethers (PBDEs), perfluorooctanoic acid (PFOA), and perfluorooctane sulfonate (PFOS) contents were determined in the rhizosphere and bulk soil. The results showed low but still detectable contents of PCBs and OCPs in the soil, substances which were banned a few decades ago. Among the OCPs, dichlorodiphenyltrichloroethane (DDT) and its metabolites reaching up to 18.2 µg kg −1 of the soil even exceeded the preventive levels for these compounds in agricultural soils, i.e. 7.5 µg kg −1 of soil. For PBDEs, PFOA, and PFOS, their contents in the soil significantly increased with sewage sludge application. The enhancement of the potential biodegradability of the POPs in the rhizosphere was confirmed only for hexachlorocyclohexane (γ-HCH), where, the level of γ-HCH increased significantly in the rhizosphere soil compared to bulk soil. Thus, natural attenuation of POPs in the soil-plant system seems to be insufficient for most of the investigated compounds.